Identifikasi Keanekaragaman dan Kelimpahan Zooplankton di Danau Sunter DKI Jakarta - Chusna, Jhihan Hanifa; Aisyah, Arina; Afandi, Ahmad Yusuf (UNIB Press, 2024)
Zooplankton in the food chain acts as the primary consumer which connects phytoplankton as producers with organisms that have higher nutritional levels, for example nekton and benthos. This research aimed to identify zooplankton diversity and abundance in Lake Sunter. This research used a purposive sampling method to take the samples, to determine station points based on the environmental conditions of the lake. The results obtained were the identification of species from the genus Candacia, Nauplius, Eudiaptomus, Tintinnopsis, Polyarthra, Brachionus, Trichocerca, Philodina, dan Polydora. The diversity index of station 1 was categorized as medium (1.32), station 2 was in the low category (0.64), and station 3 was in the medium category (1.47). The abundance value at station 1 was 26,000 Ind/L, station 2 had an abundance value of 9,302 Ind/L, and station 3 had an abundance value of 32,500 Ind/L. In conclusion, the results of research at Lake Sunter found 9 genera of zooplankton. The diversity index of Lake Sunter was in the low to medium category, which indicates that the area has high ecological pressure and the species diversity index is low. The zooplankton abundance index value was categorized as high because each station had an abundance value above 500 Ind/ L.